The Correlation between the Level of Hemoglobin and Learning Concentration on the Tenth-Grade Science Class Female Students in Senior High School of 3 Denpasar - Sari, Ni Made Sekar; Suarningsih, Ni Kadek Ayu; Antari, Gusti Ayu Ary (Journal of A Sustainable Global South; Vol 6 No 1 (2022): February 2022, 2022)
Hemoglobin   is an  iron rich  protein present in red blood cells. Female student is vulnerable of having abnormally low levels of hemoglobin (?12 g/dL) due to blood losses during monthly menstruation, which can have an impact on decreasing their concentration to learn. The purpose of this research was to determine the correlation of hemoglobin levels and learning concentration on the tenth-grade science class female students in senior high school of 3 Denpasar. It used quantitative type of research and cross-sectional study model approach. The sampling methods used simple random sampling which is totaled 122 respondents. The data collection of hemoglobin levels used digital method Easy Touch GCHb and learning concentration used questionnaire with a total of 27 statements. Based statistic test on Pearson Product Moment , it showed hemoglobin level with learning concentration on the tenth-grade science class female students in senior high school of 3 Denpasar, has a strong and positive correlation (r=0,737; p<0,05).   Keywords: Hemoglobin Level, Learning Concentration, Female Student